Comment traduire les noms d’émotion - Argyro Moustaki; Mavina Pantazara; Aggeliki Fotopoulou; Marianna Mini (Discours)
This article presents a contrastive study of how we express emotions in Modern Greek and French. We study predicate nouns denoting emotion, such as joie, angoisse, peur, colère, enthousiasme, etc. Our aim is to establish correspondences between the lexicons of emotions of these two languages. Hence, we examine the syntactic and lexical properties of the Greek and French constructions, by taking into account the aspect and style modalities, as well as the specifications of the register in relation to the lexical elements involved (namely, support verbs and nominal determinants).